1, 3-dichloro-2-propanol induced lipid accumulation by blocking autophagy flux in HepG2 cells. (30th April 2021) - Lu, Jing; Fan, Yong; Liu, Meitong; Zhang, Qian; Guan, Shuang
Graphical abstract: The mechanism of 1, 3-DCP-induced lipid accumulation by blocking autophagy flux. Abstract: Great attention has been paid to 1, 3-dichloro-2-propanol (1, 3-DCP) due to its presence in food and concerns about toxic potential as carcinogens. In our previous study, we found that long-term low-dose 1, 3-DCP exposure induced lipid accumulation in mouse liver. Recent studies have demonstrated that autophagy plays an important role in regulating lipid metabolism. So, we speculated that 1, 3-DCP induced lipid accumulation by regulating autophagy in hepatocytes. In this study, we first studied the effect of 100 μM 1, 3-DCP on autophagy flux in HepG2 cells. The data showed that 1, 3-DCP (100 μM) impaired autophagy flux mainly through the attenuation of autophagosomes via AKT/mTOR signaling pathway and inhibition of lysosomes biosynthesis. Furthermore, we demonstrated that treatment with 100 μM 1, 3-DCP for 24 h affected lipid metabolism through the colocalization of LC3 and Bodipy. We used an autophagy activator or an autophagy inhibitor to test the effect of 1, 3-DCP on lipid accumulation through detecting lipid droplets staining, triglyceride (TG) and total cholesterol (TC). The data showed that 1, 3-DCP-induced lipid accumulation was alleviated in the presence of Rapamycin (an autophagy activator). On the contrary, 1, 3-DCP-induced lipid accumulation was significantly exacerbated in the presence of an autophagy inhibitor (3-methyladenine or chloroquine). These results suggested that 1, 3-DCP might induce lipid accumulation by the impairment of autophagy flux in HepG2 cells.